Glucagon-like peptide-1 analogues - an efficient therapeutic option for the severe insulin resistance of lipodystrophic syndromes: two case reports. (December 2017) - Oliveira, Joana; Lau, Eva; Carvalho, Davide; Freitas, Paula
Abstract Background Lipodystrophic syndromes are uncommon medical conditions which are normally associated with metabolic disorders, such as diabetes mellitus, dyslipidemia, and fatty liver disease. These complications are generally difficult to treat, particularly diabetes, due to severe insulin resistance. We present two case reports of successful treatment of diabetes with glucagon-like peptide-1 analogues in patients with clinical features of lipodystrophic syndromes. Case presentation Two white women aged 49 and 60 years manifested marked central body fat deposition with severe lipoatrophy of their limbs and buttocks and pronounced acanthosis nigricans. They had hypertension, dyslipidemia, fatty liver disease, and poorly controlled diabetes (glycated hemoglobin 8.3% and 10.2%, respectively) despite the use of three classes of oral antidiabetic drugs taken in combination in the first case, and high doses of insulin in the second case. Four months after the addition of glucagon-like peptide-1 analogue to their previous treatment they both showed a pronounced improvement in metabolic control (glycated hemoglobin 5.6% and 6.2%, respectively). In the first case, a weight loss of nearly 30 kg was recorded. Conclusions We intend to demonstrate that glucagon-like peptide-1 analogues could be a valuable tool for patients with lipodystrophic disorders, probably by improving body fat distribution, with favorable results in insulin-sensitivity and glycemic control.